Chronic myeloid leukaemia with extreme thrombocytosis. (19th August 2015) - Verma, Shailendra Prasad; Subbiah, Arunkumar; Jacob, Sajini Elizabeth; Basu, Debdatta
Abstract : We report two cases of chronic myeloid leukaemia (CML) with extreme thrombocytosis. The first patient was a 65-year-old man who presented with prolonged history of upper abdominal discomfort, anorexia and two episodes of recent gum bleeds without fever or other bleeding manifestations. He was a chronic smoker with no other comorbidities. Examination revealed moderate hepatosplenomegaly. On investigation, he was found to have extreme thrombocytosis (3 500 000/mm 3 ) and leucocytosis with moderate anaemia. In view of the leucocytosis, he was investigated for CML and found to be positive for BCR-ABL by reverse transcription PCR (RT-PCR). He received imatinib 400 mg/day and achieved complete haematological response at the end of 3 months. The second patient was a 7-year-old boy who presented with fever, cough and cold of 2-week duration. Examination revealed mild hepatomegaly with palpable spleen tip. Haemogram and peripheral smear revealed moderate leucocytosis with extreme thrombocytosis (2 800 000/mm 3 ). On evaluation, he was found to be BCR-ABL positive and responded well to imatinib treatment. In both these cases, massive thrombocytosis was an unusual presentation of a well-known entity, namely, CML. This degree of thrombocytosis is usually seen only in essential thrombocytosis.